A district magistrate's call on a disaster warning: paranoid or pragmatic?. Issue 2 (15th February 2022) - Varma, Harikrishnan Ramesh; Kakani, Ram Kumar
Abstract : Theoretical basis: This case uses two key theoretical notions for discussion and analysis: Policy-trade off model by Deborah Stone is adapted to the context of decision-making during the cyclone warning [Stone, Deborah. Policy Paradox: The Art of Political Decision-Making. Third, New York: W.W. Norton & Co, 2012.]. The critical success factors in disaster response- John R. Harrald's five-stage framework is applied to analyse Case B. [Harrald, John R. "Agility and Discipline: Critical Success Factors for Disaster Response:" The ANNALS of the American Academy of Political and Social Science, 8 September 2016. https://doi.org/10.1177/0002716205285404 .]. Research methodology: This case is written with the information collected through interviews, over three months from March 2020, with Ms Ranjana Chopra (Indian Administrative Services), a senior civil servant working for the Government of Odisha, who was associated with the event in the case. Secondary sources, including newspaper reports and meteorological bulletins from the Indian Meteorological Department, is also made use of. Case overview/synopsis: Anupama Gowda was the District Magistrate of Kalinga in the state of Odisha, in the Eastern coast of the Indian peninsula. In April 2019, when the meteorological department issued a cyclone warning, she had to take a call on how to go ahead. Her team did not seem too enthused as Kalinga was away from the coast and meteorological warnings were taken as routine. The case discusses Gowda's dilemma on whether to push for full-fledged preparations or a limited preparation at least or leave it laissez-faire. She made the decision by 24th April and "what happened" serve as Case B. Complexity academic level: This case is intended to cover two key competencies: decision-making in ambiguity for public service professionals or bureaucrats and disaster response within a limited time period and resources. This case is useful for undergraduate-level foundational courses with decision-making under ambiguity as a component; in management, public policy and public administration disciplines. Executive training or short-term courses for early-career public service professionals (with no solid background in management/policy theory) on decision-making at the local administration level.